Нові дані з давньоруської писемності - Петрашенко, В.О.; Козюба, В.К. (Інститут археології НАН України, 2008)
Публікація нових епіграфічних пам’яток ХІІ ст. з Канівщини. Статья состоит из двух частей. В первой публикуется пряслице с рисунком, найденное в жилище XII в. на поселении возле с. Бучак на Каневщине. Сопоставляются знаки рисунка с руническими знаками степной зоны Европейской России VIII—XII вв. Их схожесть связывается с наличием неславянского населения на приграничной территории Руси. Во второй части публикуется фрагмент граффити, происходящий из Зарубского монастыря. Анализ его палеографических особенностей позволяет отнести надпись к концу XII в. The article comprises of two parts. The first is the publication of a whorl with the drawing found in the 12th c. dwelling in the settlement near Buchak village in Kyiv region. Marks from the drawing are compared to the runic marks of the 8th—12th cc. of the Steppe zone of European Russia. Their similarity is related to the existence of non-Slavonic population on the border lines of Rus. The second part is a publication of a fragment of graffiti from the Zarubskyj Monastery. The analysis of palaeographic peculiarities allows the authors to refer the inscription to the end of the 12th c.